Experimental study on the load bearing behavior of shored mechanically stabilized earth wall - Pang, Dongdong; Chen, Xiaoyi; Gao, Mengliang; Miao, Chenxi; Zhang, Wei (Frontiers in Earth Science, 2024)
Shored mechanically stabilized earth (SMSE) walls have been increasingly applied in the projects of widening existing roads or new construction of roads on slopes because of their good carbon emission reduction and mechanical performance. In this paper, a scaled-down model test of SMSE wall with shoring wall batter of 1H:2V was conducted to study the load-bearing behavior of SMSE wall under this terrain condition, and the results including wall deformations, earth pressures, reinforcement strains, and potential failure surface were analyzed. The results show that although the backfill near the shoring wall was not directly compressed by the load, it still slipped along the backfill-shoring wall interface. The loading created a tensile pressure zone in the upper part of the backfill-shoring wall interface, which may lead to tensile cracking. The uppermost layer of geogrid was more prone to sliding, while the tensile deformation was smaller, and its strain value was overall smaller than the strain value of the geogrid below it. As the load increases, the potential failure surface changed from a Rankine failure surface to a bilinear potential failure surface. The potential failure surface did not pass through the heel of the SMSE wall under large loads.